-x-54=-7x+54

Simple and best practice solution for -x-54=-7x+54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x-54=-7x+54 equation:


Simplifying
-1x + -54 = -7x + 54

Reorder the terms:
-54 + -1x = -7x + 54

Reorder the terms:
-54 + -1x = 54 + -7x

Solving
-54 + -1x = 54 + -7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7x' to each side of the equation.
-54 + -1x + 7x = 54 + -7x + 7x

Combine like terms: -1x + 7x = 6x
-54 + 6x = 54 + -7x + 7x

Combine like terms: -7x + 7x = 0
-54 + 6x = 54 + 0
-54 + 6x = 54

Add '54' to each side of the equation.
-54 + 54 + 6x = 54 + 54

Combine like terms: -54 + 54 = 0
0 + 6x = 54 + 54
6x = 54 + 54

Combine like terms: 54 + 54 = 108
6x = 108

Divide each side by '6'.
x = 18

Simplifying
x = 18

See similar equations:

| X+2+x+2+x+2+X+2=12 | | 1+x+4+x+7+x+10=0 | | 0.02(n-550)=105 | | 4p+3q=41 | | 12.6x=56.7 | | 6n=3n-2+2(2n+1) | | -6s-11=-2s+5 | | 9k-26=6k | | 2x+7-26=17-4x+5 | | 2xy+60-5xy=x+10+y | | -2p-6=10-10p | | 26+2x=263 | | x-32=63-4x | | 0=-X^2-6X | | 6x+8=46 | | 12x^2y+8xy+4xy^2= | | 5x+16=8x-8 | | 5x-306=20 | | 18+x=x+11+12 | | 2xy-x+40-y=5y-20+xy | | T=141.68+.75M | | -7+4m=6n-5 | | 37xsquared+35x-14= | | .2x-25=18 | | -38+3x=38-x | | 4x^2+15x-4=f(x) | | ryan=rike | | 38+(7x+1)+(10x+22)=180 | | 10b^2+7=397 | | 8(x-3)-(6-2x)=2(x-2)-5(5-x) | | 8w^2-72=0 | | .25y+2=-14 |

Equations solver categories